Practice of Dental Surgeons about Dental Splatter and Aerosol (City Dental College Journal, 2013)
Aim: This descriptive type of cross-sectional study was conducted among 105 dental surgeons working in the outpatient departments at some renowned educational institutions and a few private dental clinics in Dhaka city. Methods: The respondents were interviewed using structured questionnaire and their method of practice was noted. Results: Mean period of practice was 9.49±5.936 (1 to 27) years. The mean age in year of the respondents was 33.88±6.18 (24 to 50) years. Highest respondents were from private dental clinics (28.6%) and the rests were from educational institutions. According to educational qualifications, 65.7% were graduate dental surgeons and the rest were postgraduates. Male were more (63) in numbers than the female respondents (42). Only 9.5% practiced dental chair instrument tray and other exposed area cleaning with disinfectants between patients, 6.7% used to wrap exposed areas and change between different patients and 5.7% practiced air exhausting during dental treatment. Only 27.6% changed gloves for each patient, 71.4% dental surgeons used aprons, 96.1% dental surgeons used face masks, 74.3% respondents did not use goggles or eye protecting shields and only 4.8% dental surgeons used head caps in their daily dental practice. Of all, 5.7% dental surgeons routinely advised their patients to rinse mouth with any antiseptic mouth wash before treatment to minimize dental splatter and aerosol and 3.8% dental surgeons used high-volume suction as a routine practice during all dental treatment procedures. Conclusion: The study reveals the existing practice situation of dental surgeons of Dhaka city about cross infection control especially dental splatter and aerosol. Dental health-care personnel, dental patients and their family members are at a risk to expose to contaminated diseases due to dental splatter and aerosol. DOI: http://dx.doi.org/10.3329/cdcj.v10i2.16314 City Dent. Coll. J Volume-10, Number-2, July-2013